ESTETIKA SIMBOLIS DALAM BUSANA PENGANTIN ADAT MINANGKABAU DI PADANG - Anggia Maresa (Jurnal Filsafat "WISDOM", 2009)
AbstractMinangkabau's wedding dress is one of traditional arts in Minangkabau's society. The symbols at wedding dress are foundedpunishment and sense of morality about human deportment.Although the era have changed, the wedding dress still exists atwedding ceremonies of Minangkabau, especially in Padang. Thewedding dress shows many great aesthetic things which are combined by shapes and symbols containing morals and advices for the meaningful marriage. It is a heritage from the ancestor.Keyword: wedding dress, symbols, aesthetics, Minangkabau.